The Management of Executive, Copa, Motiva (ECM) Counseling Service in the Primary School - Hardiyanti, Dwi; Wibowo, Mungin Eddy; Haryono, Haryono; Wahyudin, Agus (The Journal of Educational Development, 2017)
The limitations and difficulties of finding professional counseling teachers with adequate competencies for the elementary school still hamper the effort of developing the counseling service program at school. 130,000 counseling teachers are still needed in junior and senior high school/equivalent, excluding the needs of counseling teachers in elementary school/equivalent. The availability of counseling teachers is far from ideal, there should be an action as a solution from the government and schools demanding that a number of schools are able to develop mechanisms related to service management and procurement of counseling teachers. Therefore, this study offers a solution through a product in the form of a guidebook resulted from of a research and development based on the standard model in the service implementation and guidance at elementary school. This research and development (R & D) study employed Borg and Gall design as well as a model design that adapts the development of McKenny. This study includes 10 procedures introduced by Borg and Gall which were modified into three stages: (1) preliminary study; (2) design development; (3) final product testing. The results show: (1) preliminary study found that the form of counseling service management model in elementary school has weaknesses, i.e. the implementation has not been referring to the principle of counseling service comprehensively, the involvement of stakeholders has not yet been maximal, the implementation was just remedial-curative and inclusive along with the learning activities. Most primary schools have not had counseling teachers yet, and there was no evaluation as feedback from the stakeholders; (2) the design development resulted in an Executive, Copa, Motiva (ECM) model as practical solution in counseling service in elementary school; (3) the final product of counseling service management has five management functions: planning, organizing, implementing, evaluating, and reporting. The five management functions in the counseling services in elementary school are used as a standard guideline for preparing the guidebooks produced from this study.